2019
DOI: 10.1155/2019/4360175
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavones and Isoflavone Glycosides: Structural-Electronic Properties and Antioxidant Relations—A Case of DFT Study

Abstract: Isoflavonoids and isoflavonoid glycosides have drawn much attention because of their antioxidant radical-scavenging capacity. Based on computational methods, we now present the antioxidant potential results of genistein (1), biochanin A (2), ambocin (3), and tectorigenin 7-O-[β-D-apiofuranosyl-(1-6)-β-D-glucopyranoside] (4). e optimized structures of the neutral and radical forms have been determined by the DFT-B3LYP method with the 6-311G(d) basis set. From the findings and thermodynamic point of view, the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…The formation of the interaction between the hydroxyl group and C4 could improve the planarity of the structure and also increase the π electrons in ring C. However, it is important to highlight that we should not neglect the influence of ketone oxygen for aromaticity due to the presence of the π electrons associated with this atom. The antioxidant activity of flavonoids was shown to be dependent on the stabilization of the O3H group through unsaturation of ring C. 14 , 46 51 Despite the presence of planarity in the molecules, the ZZ term (NICS zz ) is well aligned with the anisotropic (NICS anisotropic ) term of ring B ( Figure 5 ) and the aromaticity only occurs in the ring C of anthocyanidin (NICS zz and NICS isotropic terms). This result corroborates the high antioxidant activity previously reported for an anthocyanidin analogue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the interaction between the hydroxyl group and C4 could improve the planarity of the structure and also increase the π electrons in ring C. However, it is important to highlight that we should not neglect the influence of ketone oxygen for aromaticity due to the presence of the π electrons associated with this atom. The antioxidant activity of flavonoids was shown to be dependent on the stabilization of the O3H group through unsaturation of ring C. 14 , 46 51 Despite the presence of planarity in the molecules, the ZZ term (NICS zz ) is well aligned with the anisotropic (NICS anisotropic ) term of ring B ( Figure 5 ) and the aromaticity only occurs in the ring C of anthocyanidin (NICS zz and NICS isotropic terms). This result corroborates the high antioxidant activity previously reported for an anthocyanidin analogue.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the aromaticity of the structures can contribute to understand the antioxidant mechanism. The number and position of hydroxyl groups have been widely studied regarding the antioxidant activity. , For example, for luteolin, it was demonstrated that by removing the O3H group in ring C, the antioxidant activity consequently decreases . Moreover, the importance of ring C unsaturation was pointed out, which allows electron delocalization for stabilization of the aryloxyl radical .…”
Section: Resultsmentioning
confidence: 99%
“…To correct the zero-point energy (ZPE) and to confirm the presence of ground states lacking imaginary frequencies, vibrational frequencies were calculated at the same level of theory. The integral equation formalism polarizable continuum model (IEF-PCM) has been employed for estimating solvent effects [26,27].…”
Section: Methodsologymentioning
confidence: 99%
“…Mechanistic studies have suggested three pathways for radicals scavenging property: HAT (H atom transfer), SET-PT (single electron transfer-proton transfer), and SPLET (Sequential Proton Loss Electron Transfer) [26][27][28][29]. The first mechanism, HAT, involves an H-atom transfer process, in which a hydrogen atom is removed from a flavonoid antioxidant compound to a free radical (R•), which is illustrated as follows:…”
Section: Methodsologymentioning
confidence: 99%
“…This threshold is proposed 46 , 101 , 112 because a small energy difference between conformers could indicate an interconversion process: rotatability of OH groups 165 or side chains, 84 bonds deformation due to keto–enol tautomery, 21 shift in E/Z-conformers equilibria, 133 and bending of dihedral angles. 16 , 20 , 28 , 33 , 50 , 67 , 128 , 165 They can all modulate hydrogen bonds, electrons cloud delocalization, and polarizability, as well as radical accessibility to specific sites of an antioxidant. Furthermore, the molar fraction cannot be too low if the compound is desired to pass biological barriers.…”
Section: Preliminary Concernsmentioning
confidence: 99%